The impact of lockdown on symptoms and health status of patients with chronic airway diseases: An appraisal of patient perceived impressions - Parthasarathi Bhattacharyya; Sikta Mukherjee; Moumita Chatterjee; Dipanjan Saha; Sayoni Sengupta; Debkanya Dey (Lung India, 2023)
Background: The pandemic-specific lockdown may influence the health status of patients with chronic airflow obstruction (CAO) as COPD, COPD-PH, and chronic asthma. Objectives: To find the impact of the lockdown on symptoms, and the degree of perceived change in physical activity and emotional health with possible reasons including the indicators of ambient air pollution. Methods: A cohort of CAO patients was telephonically enquired regarding their perceived well-being in symptom status, physical activity, and emotional health with the perceived contribution from plausible reasons (regular medication, simple food, no pollution, and family attention) for the change; all being expressed in percentages. The change in symptom scores as 0-39, 40-79, and 80-100 were regarded as 'low', 'medium', and 'high' respectively. The impact of the individual contributing factor was calculated statistically. The assessment of the CAT (COPD assessment test) score and the ambient air pollution (PM2.5 and PM10) was also done for their association with well-being. Results: There was a universal improvement (p < 0.5) in COPD (n = 113), COPD-PH, (n = 40), and chronic asthma, (n = 19) as regards symptoms, physical activity, and emotional health that tallies to overall and individual change in CAT score. There were concomitant reductions in PM10 and PM2.5 levels during the lockdown compared to the same period of the previous year. All the four listed factors contributed with the 'no/low pollution' and 'simple food being the most important; on acting together, they reduced the moderate and severe symptoms impressively. Conclusion: Reduced air pollution and simple food appear most important for the improvement of CAO patients during the lockdown period.